Credit risk management - Drlíčková, Marie; Kielar, Petr, 1965-; Palán, Luděk; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2019)
This bachelor thesis deals with credit risk of commercial banks. The aim of the thesis is to describe methods used to manage credit risk of the largest Czech banks and to examine the current situation in the Czech banking sector: to evaluate the level of regulatory capital, to describe risk exposures and structures of loans in the system as a whole and separately in the three selected banks. The data is drawn from statistics published by the Czech National Bank, financial results and annual reports of the individual banks. In the theoretical part, credit risk, credit risk management methods and Basel concepts are characterised. The empirical part focuses on the comparison of selected methods in the Czech banks.
Vedoucí práce: Petr Kielar
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor bakal. práce]; bakalářské práce; bachelor's theses